Long-term monitoring following Tamarix spp. biological control suggests variable success - McIsaac, Liana, author; Hufbauer, Ruth, advisor; Norton, Andrew, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2026)
Invasive plants can cause a broad swathe of environmental and economic problems. One means to alleviate the intensity of such problems is through the introduction of classical biological control agents. Particularly for woody plants, biological control may take many years, and thus long-term monitoring of biocontrol programs may be useful to evaluate the effects of biological control on target plants and the surrounding plant community. Here, we use long-term monitoring to evaluate performance of the invasive tree Tamarix spp. and shifts in understory vegetation up to 22 years following release of Diorhabda (Coleoptera: Chrysomelidae) biological control agents. We combine three datasets from sites in Colorado and Utah, and include new data, focusing on Tamarix volume and understory vegetation. Average tree volume declined in most sites, though not as substantially as might be expected from shorter-term studies. Cover of both native and introduced plant species decreased, while species richness remained fairly stable. These findings suggest that additional action may be necessary to further reduce Tamarix performance and manage for desired plant communities, particularly in some sites. Our study offers lessons for others embarking on long-term monitoring, including implementing experimental controls and establishing shared and consistent approaches to data collection, including detailed metadata.
Keywords: Diorhabda; long-term monitoring; Tamarix; invasive species; biological control; native plants